FRI0075 A multi-biomarker disease activity (vectra™ da algorithm) score and components are associated with sustained clinical remission in rheumatoid arthrits: the remira study. (23rd January 2014) - Ma, M. H.; Li, W.; Defranoux, N.; Kingsley, G. H.; Scott, D. L.; Cope, A. P.
Abstract : Background: Therapeutic advances have made low disease-activity states (LDAS) and remission increasingly common for patients with rheumatoid arthritis (RA) [1 ]. In order to achieve and maintain tight-control of disease activity, it is essential to identify predictors of sustained remission A multi-biomarker disease activity (MBDA) score has been validated to assess disease activity in patients with RA. We examined these serum biomarkers as predictors of sustained remission. Objectives: To explore the use of the MBDA score and its components to predict sustained remission in patients from the REMIRA cohort. Methods: The study was conducted on 95 patients from the Remission in RA (REMIRA) cohort (disease duration <10 years, stable therapy > 6 months and DAS28-ESR<3.2) [1 ]. Patients were assessed every 3 months for 1 year. Serum concentrations of VCAM-1, EGF, VEGF-A, IL-6, TNF-RI, YKL-40, MMP-1, MMP-3, leptin, resistin, SAA, and CRP were measured at baseline by multiplex immunoassay and combined using the validated Vectra DA algorithm to generate a MBDA score (range 1-100) [2 ]. Clinical remission was defined by EULAR 2011 Boolean criteria and SDAI, CDAI, and DAS28-ESR scores. 'Sustained remission' was defined as achieving remission at all time points. 'Intermittent remission' was defined as remission at ≥1 time point but not all. Results: The mean (±SD) baseline (BL) characteristics were: age 56 (±17), disease duration 50 months (±31), 61% female and 88% were RF positive, DAS28-ESR 2.10 (±0.96) and MBDA score 31.4 (±12.66). At BL, 31%, 49%, 49% and 67% of these patients were in remission according to Boolean, SDAI, CDAI and DAS28-ESR criteria respectively. Of those in remission, 28%, 48%, 50% and 69% achieved sustained remission using the same criteria over 1 year. Lower BL MBDA score, CRP, SAA, and IL-6 were associated with sustained remission defined by DAS28-ESR, SDAI, CDAI and Boolean criteria. The median BL MBDA score was <25 in all sustained remission groups. Baseline MBDA score inversely correlated with the proportion of visits in remission for all remission criteria. In patients with ≤1 missing data point for each clinical measurement (n=68), BL MBDA score, CRP, SAA and IL-6 could stratify between no, intermittent and sustained remission for at least one of the remission criteria. Only MBDA score was able to stratify across all 4 criteria. By using logistic regression, BL MBDA was not found to be an independent predictor of sustained DAS28-ESR remission if given BL DAS28-ESR. Conclusions: This study showed that only a subset of patients in LDAS at BL achieved sustained clinical remission over a 1 year period. The rates of sustained remission differed across the 4 remission criteria analyzed. Baseline MBDA score, IL6, SAA, CRP and leptin were associated with sustained remission. Acute phase response markers IL6, SAA and CRP were able to stratify between no, intermittent and sustained remission groups suggesting that persistent inflammation is significant even at low levels of disease activity. References: Ma MHY et al., Remission in early RA. J Rheumatol.2010; 37(7):1444 Curtis JR, et al., Validation of a novel multi-biomarker test to assess rheumatoid arthritis disease activity. Arthritis Care & Research 2012; 64(12):1794 Disclosure of Interest: M. Ma Grant/research support from: NIHR, W. Li Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, N. Defranoux Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, G. Kingsley: None Declared, D. Scott Grant/research support from: NIHR, A. Cope Grant/research support from: Arthritis Research UK